Effect of follicle size and atresia grade on mitochondrial membrane potential and steroidogenic acute regulatory protein expression in bovine granulosa cells. Issue 6 (18th December 2018) - Ostuni, Angela; Faruolo, Maria Pina; Sileo, Carmen; Petillo, Agata; Boni, Raffaele
Summary: During follicular development, granulosa cells undergo functional and structural changes affecting their steroidogenic activity. Oestrogen synthesis mainly occurs in the endoplasmic reticulum and relies on aromatase activity to convert androgens that arise from theca cells. In the present study, indicators of mitochondria-related steroidogenic capacity, as steroidogenic acute regulatory (StAR) protein expression and mitochondrial membrane potential (MMP), have been evaluated in bovine granulosa cells (GCs) and related to follicle growth and atresia. Atresia was estimated by morphological examination of follicle walls and cumulus–oocyte complexes (COC) and assessed by terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick end labeling (TUNEL) assay for apoptosis detection. Bovine ovarian follicles were macroscopically classified according to their atresia grade and grouped into small, medium or large follicles. After follicle opening, the COCs were morphologically classified for follicle atresia and the GCs were collected. Granulosa cells were fixed for immunofluorescence (IF) and TUNEL assay, frozen for western blotting (WB) or freshly maintained for MMP analyses. StAR protein expression was assessed using both IF and WB analyses. The follicle atresia grade could be efficiently discriminated based on either follicle wall or COC morphological evaluations. Granulosa cells collected from small non-atretic follicles showed a higher ( P <0.01) MMP and WB-based StAR protein expression than small atretic follicles. For IF analysis, StAR protein expression in large atretic follicles was higher ( P <0.05) than that in large non-atretic follicles. These results suggest a role played by mitochondria in GC steroidogenic activity, which declines in healthy follicles along with their growth. In large follicles, steroidogenic activity increases with atresia and is possibly associated with progesterone production.